Efficacy and safety of ascending dosages of albendazole against Trichuris trichiura in preschool-aged children, school-aged children and adults: A multi-cohort randomized controlled trial. (May 2020) - Patel, Chandni; Coulibaly, Jean T.; Schulz, Jessica D.; N'Gbesso, Yves; Hattendorf, Jan; Keiser, Jennifer
Abstract: Background: The efficacy of the widely used albendazole against the soil-transmitted helminth Trichuris trichiura is limited; yet optimal doses, which may provide increased efficacy, have not been thoroughly investigated to date. Methods: A randomized-controlled trial was conducted in Côte d'Ivoire with preschool-aged children (PSAC), school-aged children (SAC), and adults infected with T. trichiura . Participants were randomly assigned (1:1:1:1) using computer-generated randomization. PSAC were randomized to 200 mg, 400 mg, 600 mg of albendazole or placebo. SAC and adults were randomized to 400 mg, 600 mg, 800 mg of albendazole or placebo. The primary outcome was cure rates (CRs) against trichuriasis. Secondary outcomes were T. trichiura egg reduction rates (ERRs), safety, CRs and ERRs against other soil-transmitted helminths. Outcome assessors and the trial statistician were blinded. Trial registration at ClinicalTrial.gov: NCT03527745. Findings: 111 PSAC, 180 SAC, and 42 adults were randomized and 86, 172, and 35 provided follow-up stool samples, respectively. The highest observed CR among PSAC was 27·8% (95% CI: 9·7%–53·5%) in the 600 mg albendazole treatment arm. The most efficacious arm for SAC was 600 mg of albendazole showing a CR of 25·6% (95% CI: 13·5%–41·2%), and for adults it was 400 mg of albendazole with a CR of 55·6% (95% CI: 21·2%–86·3%). CRs and ERRs did not differ significantly among treatment arms and flat dose-responses were observed. 17·9% and 0·4% of participants reported any adverse event at 3 and 24 h follow-up, respectively. Interpretation: Albendazole shows low efficacy against T. trichiura in all populations and doses studied, though findings for PSAC and adults should be carefully interpreted as recruitment targets were not met. New drugs, treatment regimens, and combinations are needed in the management of T. trichiura infections. Funding: Bill and Melinda Gates Foundation .